Determination of suitable sex for morphological comparison in populations of Aphanius dispar using geometric morphometrics - S Eagderi email (‬‭Majallah-i ̒Ilmī-i Shīlāt-i Īrān, 2017)
Sexual dimorphism is a phenomenon among some fish species such as the members of the genus Aphanius. Among species with sexual dimorphism, morphological analysis needs to be performed separately. Hence, this investigation was carried out to determine suitable sex of Aphanius dispar for morphological studies. A total 180 specimens (male and female) were collected from populations of Sarbaz, Mehran and Shour rivers. Digital picture of speciments were taken from their left sides and then 17 landmark points cover their body shape were determined and digitized using tpsDig2 software. The data after GPA, were analyzed using PCA, CVA and MANOVA. The results revealed that studied population can be differitiated based on their body shap but between male and female of the Shour and Mehran rivers did not found significant different ib their separate analysis. Sexual dimorphism in the head and trunk seems to be a general feature in A. dispar. Based on the results in A. dispar, males can be suggested as proper sex for morphometric studies.